2021
DOI: 10.1002/ece3.8015
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene dynamics of the Eurasian steppe as a driving force of evolution: Phylogenetic history of the genus Capsella (Brassicaceae)

Abstract: Capsella is a model plant genus of the Brassicaceae closely related to Arabidopsis. To disentangle its biogeographical history and intrageneric phylogenetic relationships, 282 individuals of all five currently recognized Capsella species were genotyped using a restriction digest‐based next‐generation sequencing method. Our analysis retrieved two main lineages within Capsella that split c. one million years ago, with western C. grandiflora and C. rubella forming a sister lineage to the eastern lineage consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 95 publications
(158 reference statements)
1
9
0
Order By: Relevance
“…Many other arctic and steppe‐tundra species used the BLB as a dispersal route and glacial refugium, but the BLB also remained as a biological barrier, as evidenced by a number of animal species, for example wooly rhinoceros, musk‐oxen, the North American river otter, American marten and several groups of steppe‐tundra beetles, including cold‐adapted weevils and leaf beetles that are restricted to only one side of the BLB (Combe et al, 2021; Elias & Crocker, 2008; Meiri et al,2014 2015). Our study thus contributes to the understanding of the evolutionary history of temperate steppe regions, including their intercontinental disjunctions summarized in comprehensive reviews (Barbolini et al, 2020; Hurka et al, 2019) and advanced methods in phylogeography (Kirschner et al, 2020; Seidl et al, 2020; Volkova et al, 2017; Žerdoner Čalasan, German, et al 2021; Žerdoner Čalasan, Hurka, et al 2021).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Many other arctic and steppe‐tundra species used the BLB as a dispersal route and glacial refugium, but the BLB also remained as a biological barrier, as evidenced by a number of animal species, for example wooly rhinoceros, musk‐oxen, the North American river otter, American marten and several groups of steppe‐tundra beetles, including cold‐adapted weevils and leaf beetles that are restricted to only one side of the BLB (Combe et al, 2021; Elias & Crocker, 2008; Meiri et al,2014 2015). Our study thus contributes to the understanding of the evolutionary history of temperate steppe regions, including their intercontinental disjunctions summarized in comprehensive reviews (Barbolini et al, 2020; Hurka et al, 2019) and advanced methods in phylogeography (Kirschner et al, 2020; Seidl et al, 2020; Volkova et al, 2017; Žerdoner Čalasan, German, et al 2021; Žerdoner Čalasan, Hurka, et al 2021).…”
Section: Discussionmentioning
confidence: 75%
“…The greatest diversity and expansion of steppe communities occurred in northern Eurasia during the glacial periods of the Pleistocene, as evidenced by diversification and expansion of typical steppe taxa such as Capsella Medik., Clausia aprica (Stephan) Korn.‐Trotzky, Goniolimon speciosum (L.) Boiss., Sisymbrium L. and Krascheninnikovia ceratoides (L.) Gueldenst. (Franzke et al, 2004; Seidl et al, 2020; Volkova et al, 2017; Žerdoner Čalasan, German, et al 2021; Žerdoner Čalasan, Hurka, et al 2021). The same likely holds true for A .…”
Section: Discussionmentioning
confidence: 99%
“…As an extremely abundant and widespread plant on the planet, C. bursa-pastoris is an important model organism for studies in a wide variety of areas including the evolutionary ecology of weeds (Nutt et al 2006;Hintz et al 2006;Choi et al 2019;Žerdoner Čalasan et al 2021) and genome evolution following hybridization and polyploidization (Hurka and Neuffer 1997;Slotte et al 2007;Kasianov et al 2017). Because it exhibits a wide range of genetic variation among populations, many studies have looked at patterns across its geographic range to examine the evolutionary mechanisms involved (Slotte et al 2007;Neuffer 2011;Begg et al 2012;Toorop et al 2012).…”
Section: (B) Beneficialmentioning
confidence: 99%
“…At a lower taxonomic level, namely the species level, various studies place the beginning of the spread and diversification of the present-day steppe species between the Early Pleistocene and the Holocene, and the areas of origin of these species from the Caucasus region at the border between Europe and Asia to the Altai Mountains region in Asia, for example for Astragalus onobrychis L., Capsella orientalis Klokov, Clausia aprica (Stephan ex Willd.) Korn.-Trotzky and Krascheninnikovia ceratoides (L.) Gueldenst 11 , 12 , 14 , 16 , 17 . Other species descended from Euro-Siberian/Circumboreal groups.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular phylogenetic studies have confirmed that many steppe plants belong to genera or species groups within genera that originated in the Irano-Turanian floristic region such as for example the genera Astragalus, Camelina, Capsella, Clausia, Dontostemon, Krascheninnikovia and Sisymbrium as well as various species groups within Allium [8][9][10][11][12][13][14][15] . At a lower taxonomic level, namely the species level, various studies place the beginning of the spread and diversification of the present-day steppe species between the Early Pleistocene and the Holocene, and the areas of origin of these species from the Caucasus region at the border between Europe and Asia to the Altai Mountains region in Asia, for example for Astragalus onobrychis L., Capsella orientalis Klokov, Clausia aprica (Stephan ex Willd.)…”
mentioning
confidence: 98%